2006
DOI: 10.1111/j.1540-8167.2006.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

External and Endoluminal Analysis of Left Atrial Anatomy and the Pulmonary Veins in Three‐Dimensional Reconstructions of Magnetic Resonance Angiography: The Full Insight from Inside

Abstract: Both ex 3D and en 3D reconstructions of MRA precisely visualize the complex LA anatomy. Exact determination of PV ostial geometry is facilitated with en 3D and provides important anatomical information for the PVI strategy. According to our data, individual encircling of every PV is strongly discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 39 publications
5
35
2
Order By: Relevance
“…6 -8 The anatomy of left-sided PVs constitutes a challenge to antral CCL ablation mostly due to the muscular ridge between the PVs and the left atrial appendage that is a narrow (,5 mm) structure in the majority of patients, containing thick myocardium especially in its superior part. 9,10 Accordingly, the majority of CGs (27 out of 40, 68%) after completion of single left-sided CCLs was located at the anterior ridge ( Figure 1B). The second most common site for residual conduction into the left-sided PVs was the LA roof (9 out of 40, 23%).…”
Section: Discussionmentioning
confidence: 99%
“…6 -8 The anatomy of left-sided PVs constitutes a challenge to antral CCL ablation mostly due to the muscular ridge between the PVs and the left atrial appendage that is a narrow (,5 mm) structure in the majority of patients, containing thick myocardium especially in its superior part. 9,10 Accordingly, the majority of CGs (27 out of 40, 68%) after completion of single left-sided CCLs was located at the anterior ridge ( Figure 1B). The second most common site for residual conduction into the left-sided PVs was the LA roof (9 out of 40, 23%).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study, which evaluated the distance between the fossa ovalis and each PV using MRI, showed that the mean distance was shortest in the RIPV (20.2 mm) among the 4 PVs. 9 The longitudinal diameter of a fully expanded cryoballoon is approximately 24 mm, which may be inadequately large, especially for patients with ventral orientation of the RIPV because the PV ostium deviates closely to the atrial septum. Although the RSPV shows a ventral orientation in almost all patients, isolation of this PV using a cryoballoon is much easier than for the RIPV.…”
Section: Geographic Parameters Of Ipvs On Ct Imagesmentioning
confidence: 99%
“…As previously described, the distance between the fossa ovalis and anterior inferior border of the RPVs is short. 15 To allow RN to this region, a rather anterior transseptal puncture site (medial quarter of the fossa ovalis) is advisable.…”
Section: Navigation Propertiesmentioning
confidence: 99%